Sudan bans sorghum exports - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Sudan has banned exports of its staple food sorghum because of a drop in sorghum reserves and an expected fall in output in 2000. Farmers in al-Gedaref, the main producer state, reported in mid-2000 that insects and pests sorghum midges, rats,...